PENGARUH RASIO CAMEL TERHADAP RETURN SAHAM PADA PERUSAHAAN PERBANKAN YANG GO-PUBLIC DI BEI PERIODE 2009-2011 (Students' Journal of Accounting and Banking, 2013)
The Purpose of this reseach is to analyze the influence of Capital Adequacy Ratio (CAR), Return On Risked Assets (RORA), Operating expense to operating income (OEOI), Earning Per Share (EPS), and Loan to Deposit Ratio (LDR) of Stock Return in the Go-Public Commercial Bank in Indonesian Stock Exchange (ISX) period 2009 - 2011. Population of this research are 30 Commercial Bank that resgistered in Indonesian Stock Exchange from 2009 till 2011. Data on this research are coming from Indonesian Stock Exchange (ISX). Sample are choosen by purposive sampling method at least 25 company. Data’s test technique by using multiple linear regression analyze.The result show variable that has significant influence against stock return is Earning Per Share (EPS) variable, whereas Capital Adequacy Ratio (CAR), Return On Risked Assets (RORA), Operating expense to operating income (OEOI), and Loan to Deposit Ratio (LDR) have no significant influence against stock return.Keywords : Capital Adequacy Ratio (CAR), Return On Risked Assets (RORA), Operating expense to operating income (OEOI), Earning Per Share (EPS), Loan to Deposit Ratio (LDR) and Stock Return.